Kajian Kombinasi Ekstrak Daun Physalis angulata dan Daun Cassia angustifolia dengan Rasio 50:50 sebagai Green Inhibitor untuk API 5L dalam Larutan HCl 1M: Kajian Green Inhibitor tipe campuran untuk API 5L dalam Larutan HCl - Triska Adelia Ni Luh; Khalisha Rizqi Olga Pramono; Johny Wahyuadi Soedarsono; M. Yudi M. Solihin (Recent in Engineering Science and Technology, 2024)
The effect of combination of Physalis angulata leaf and Cassia angustifolia leaf extract as green inhibitor with a 50:50 ratio for API 5L steel was investigated. This experiment was carried in 1M HCl solution by using different concentrations as variables which is 10 ml, 30 ml, and 50 ml inhibitor extracts. Evaluation of this experiment was performed using potentiodynamic polarization and EIS. The antioxidant compound was investigated using FTIR and was found to be flavonoid. It was found that the capability of the inhibitor to inhibit the steel surface from the environment increases with increasing concentration, which 50 ml concentration is found to have the best efficiency of all concentrations. Combination of Physalis angulata leaf and Cassia angustifolia leaf extract is identified as mixed-type inhibitor with predominant cathodic effectiveness. The adsorption of this inhibitor on the steel surface was predominantly through physisorption and obeyed Langmuir adsorption isotherm.